Penerapan data mining dengan metode naïve bayes untuk memprediksi calon terjamin potensial - Khoirunnisa, Nurfitria; Nugroho, Imam Ma'ruf; Muhyidin, Yusuf (Journal of Information System, Applied, Management, Accounting and Research, 2022)
Now this credit guarantee business in Indonesia is growing, it is because the high public interest in doing credit. PT XYZ is one of the state-owned company engaged in the Credit Guarantee in Indonesia. Constraints currently faced by the PT XYZ is the absence of a system that can help predict potential candidate criteria guaranteed. Given these predictions, helping the company took the decision to provide a guarantee to secure potential candidates. Data mining is a new and useful technologies to help companies find the most important information from enterprise data warehouses that were previously considered useless. This data is processed by the method of classification is further analyzed using Naive Bayes. This analysis using UML (Unified Modeling Language) as tools. The expected outcome of this research is the analysis of the proposed system that can help companies to make decisions underwriting.